Zikir dan Pengaruhnya terhadap Ketenangan Jiwa di Era Modern menurut Al-Qur’an - Rafikah Marhani Hsb; Ali Akbar; Ghina Adilah; Izzi Munaya Putri (ejournal.nurulqadim.ac.id, 2024)
In the modern world filled with pressure, many individuals experience stress and anxiety that disrupt their inner peace. Dhikr, as a spiritual practice in Islam, offers a solution for achieving tranquility and true happiness. This research analyzes the influence of dhikr practices taught in the Qur'an on individuals' peace of mind and the spiritual dimensions of dhikr as a means to cope with stress. Through a library study, it was found that dhikr is not just verbal recitation but a deep spiritual experience that brings individuals closer to Allah SWT. Consistent practice of dhikr helps individuals attain inner peace and overcome emotional disturbances. There are three forms of dhikr—dhikr jali, dhikr khafi, and dhikr haqiqi—which reflect levels of depth in remembering Allah. Therefore, it is recommended that individuals integrate dhikr into their daily lives and that social institutions organize programs supporting dhikr practices. Further research is also needed to explore the effectiveness of dhikr in facing the challenges of modern life